A Biowaste Treatment Technology Assessment in Malawi - Wrixon Mpanang’ombe; Elizabeth Tilley; Imanol Zabaleta; Christian Zurbrügg (Recycling, 2018)
In the city of Blantyre, much of the generated municipal waste is biowaste, typically mixed with other waste fractions and disposed at the city’s dumpsite. Energy and nutrients could be recovered; however, with many biowaste options available, choosing what technology to implement is difficult. Selecting Organic Waste Treatment Technology (SOWATT) is a tool that supports decision making for selecting a biowaste treatment option considering social, technical, and environmental aspects. SOWATT was used to evaluate options for Blantyre’s Limbe Market. Anaerobic digestion, black soldier fly processing, slow pyrolysis, in-vessel composting, windrow composting, vermicomposting, and wet-biomass-briquetting were considered as options. The performance of each alternative was assessed based on five objectives by government, NGO, and market-based stakeholders in order to determine the most acceptable option for the greatest number of people: something that is rarely done, or if it is the preferences are not rigorously quantified (e.g., stakeholder workshops) and/or weighted against specific objectives. However, given the novelty of the ranking-solicitation process, some participants struggled with the variety of options presented, and further iterations of SOWATT will address this limitation. Ultimately, vermicomposting scored highest of all alternatives and could best achieve the five objectives as prioritized by the stakeholders when implemented.